Upaya Meningkatkan Kontribusi Belajar Anak yang Efektif - Ghina Hanifah; Intan Raudhatul Jannah; Salmaini Safitri Syam; Nur Azmi Alwi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
An effective learning process is the foundation or main idea in developing children's potential. Children's active contribution in the learning process is an important indicator of children's learning success. This article aims to analyze efforts that can be made to improve children's learning contributions effectively both from internal and external aspects. This study uses a qualitative, participatory, and daily life-relevant approach that can increase children's activeness in learning. Moreover, guidance from both parents and teachers is essential in fostering children's participation in learning. Collaboration between schools and families is a key factor in creating a supportive learning environment. Thus, efforts to improve children's learning contributions require not only the right pedagogical approach, but also an approach from the school, family, and social environment that supports the creation of a conducive, inclusive, and enjoyable learning atmosphere.